Postoperative Anesthesia After Simultaneous Operations in Gynecological Patients (Texas Journal of Medical Science, 2021)
The work is based on the material based on the experience of simultaneous operations on the organs of the abdominal cavity and pelvis, accumulated in the 1st SamMI clinic from September 2018 to March 2021 inclusive. In total, simultaneous operations were performed in 190 patients during this period.